Role of CRF-R1 in Social Defeat Stress Escalated Voluntary Ethanol Consumption in CFW Mice. - Norman, Kevin J. (Tufts Archival Research Center, 2014)
Abstract: Stress can play a role in alcohol and substance abuse, but the neurobiological mechanisms that underlie this relationship are unclear. The current study pharmacologically tested the role of corticotropin-releasing factor type-1 receptors (CRF-R1) in ethanol drinking following social defeat stress. Adult, male CFW mice were exposed to either 15 (moderate) or 30 (severe) attack bites for 10 consecutive days using the resident/intruder paradigm. Ten days after the final social defeat, mice were tested for the expression of locomotor sensitization following a 2 g/kg intraperitoneal (i.p.) ethanol challenge. Daily, voluntary 20% ethanol and water intake was measured during a 3 week period of continuous access to two bottle free choice. Doses of a CRF-R1 antagonist, CP-376,395 (10, 17, and 30 mg/kg, i.p.), were administered, and ethanol and water drinking were recorded 2, 4, and 24hrs after drug administration for stressed and non-stressed mice. We found that mice that experienced the severe stress, but not the moderate, during social defeat stress period consumed more ethanol than non-stressed controls. CP-376,395 decreased ethanol intake of the high ethanol drinkers in a dose-dependent manner during the initial 2 hours compared to the low ethanol drinkers; after 4 hours the drug effect was only observed at the highest dose. This pattern suggests that more intense and longer social stressors escalate ethanol consumption, but not lower intensity and shorter duration stressors. Previous exposure to ethanol access results in a delayed stress-induced escalation of ethanol drinking. CRF-R1 may play a critical role in mediating stress-induced ethanol consumption. Ongoing studies using an operant conditioning procedure suggest that socially defeated CFW mice have increased motivation for alcohol. It is anticipated that lower HPA axis activation and limbic CRF and dopamine will differentiate the stress mechanisms that engender escalated alcohol consumption.